Applications of Virtual Environments in Human Factors Research and Practice. (November 2019) - Spain, Randall; Goldberg, Benjamin; Khooshabeh, Pete; Krum, David; Biro, Joshua; Linder, Courtney; Stanley, Laura; Tredinnick, Ross; Ponto, Kevin; Gisick, Logan; Pierce, Matthew; Keebler, Joseph; et al.
Virtual reality, augmented reality, and other forms of virtual environments have the potential to dramatically change how individuals work, learn, and interact with each other. A key objective of human factors research and practice is to determine how these environments should be designed to maximize performance efficiency, ensure health and safety, and circumvent potential human virtual environment interaction problems. This session will demonstrate some of the distinct and diverse uses of virtual reality, mixed reality, and virtual environments in an alternative format. The session will begin with each demonstrator providing a brief overview of their virtual environment and describing how it has been used to address a particular problem or research need. Following the description portion of the session, all demonstrations will be set-up around the room, and session attendees will be encouraged to directly interact with the environment and ask demonstrators questions about their research and inquire about the effectiveness of using their virtual environment for research, training, and evaluation purposes. The overall objective of this alternative session is to provoke ideas among the attendees for how virtual reality, mixed reality, and virtual environments can help address their research, training, education or business needs.